The public procurement system in Belarus: a regional aspect - Krivorotko, Yuri (Socialiniai tyrimai, 2014)
The paper presented here is the country research and has an analytical character concerning a regional aspect of the public procurement system in Belarus. Stages of the public procurements system’s formation and its legislative base and the development of the electronicization of purchases are considered. The public procurement system at the sub- national level is analyzed and weak points are emphasized. Corruption aspects and ways of their minimization in the public procurement activity are showed. Debatable issues and ways of procurement activity improvement in Belarus regions are presented.The methodology of research is based on the analysis of a series of data on public procurements in the regions of Belarus, including budgetary expenditures on public procurement in the local governments of the Belarus regions and the e-auctions procurement at the Universal Commodity Exchange. Statistical data for analysis was obtained from official sources, such as the State Statistics Committees, Ministry of Finance, Open Joint Stock Company (OJSC) Belarusian Universal Commodity Exchange, and on-line databases of analytical centres working in this field, etc.
Keywords: budget expenditures; central budget; closed tender; corruption; e-auction; exchange bidding; expenditure assignment; fiscal decentralization; local budgets; open tender; public procurements; request for quotation; single source procurement; sub-national budgets